Checklist of the Iranian ants (Hymenoptera: Formicidae): additions and updates - Khalili-Moghadam, Arsalan; Salata, Sebastian (Zootaxa, 2026)
This checklist presents the results of a survey of the available literature, which identified and catalogued ants associated with different habitats in Iran. New ant species and distribution updates omitted from the previous checklists published in 2023 and 2008 are presented. A total of 381 taxa (379 species and two subspecies) belonging to 46 genera and seven subfamilies are listed. The most speciose genera are Camponotus Mayr, 1861, Cataglyphis Foerster, 1850, and Messor Forel, 1890, with 48, 45, and 45 species, respectively. As many as 60 species records from 15 genera and three subfamilies are considered doubtful and removed from the checklist. 30 species and three subspecies from 13 genera and four subfamilies have been described from Iran. Although Iran is located in the Palearctic, some ant species from the Oriental and Afrotropical regions are part of its fauna. Because many regions of Iran remain unstudied, true species richness in Iran is most-likely substantially higher.